Saatnya amandemen ke-5 UUD 1945 - Marthias, Phiodias SM (Yayasan Mitra Persada Nusantara, 2024)
This article proposes the fifth amendment to the 1945 Constitution by introducing quattuor politica to replace trias politica. So that national intellectual groups can play a full role in national development to overcome the stagnation in national capacity development. This state of stagnation has a broad impact on current development achievements. Among them, Indonesia's failure to become an industrial country and hampered mastery of science and technology. Scientific judgment of 79 years of national development policy, has been almost neglected. The conclusion be based on some facts and analysis of 79 year Indonesia's transformation as scientific phenomenon. This has an impact on Indonesia's current development challenges which are related to the improper application of scientific principles. Such as the failure to become an industrial country, still high number of corrupt practices, low achievement of current economy compared to China and Republic of Korea and high cost economy. It indicates that the role and contribution of the national intellectual community in the development is low and limited due to obstruction of trias politica practices. Introducing quattuor politica through the constitutional amendment is to enrich trias politica concept. It will empower the intellectual community as the guardian of the national capacity building by taking care of scientific principles consistently in developing the national development methodology. It is align with the mandate of Preamble of the 1945 Constitution, values of the second norm of Pancasila - Just and civilized humanity - and the nature of the practice of civilization. The principles of empiricism and the scientific phenomenon of civilization developments are the major premise of the research.